Odpowiedź :
Odpowiedź:
(a-b)^2 = a^2 - 2ab + b^2
a) 4x^2 - 4x + 1
(a+b)^2 = a^2 + 2ab + b^2
b) 9x^2 + 12xy + 4y^2
(a-b) (a+b) = a^2 - b^2
c) 4x^2 - 16
Korzystamy ze wzorów skróconego mnożenia:
[tex](a-b)^{2} = a^{2}-2ab + b^{2}\\\\(a+b)^{2} = a^{2}+2ab + b^{2}\\\\(a-b)(a+b) = a^{2}-b^{2}[/tex]
[tex]a) \ (2x-1)^{2} = (2x)^{2}-2\cdot2x\cdot1 + 1^{2} = \boxed{4x^{2}-4x+1}\\\\b) \ (3x+2y)^{2} = (3x)^{2}+2\cdot3x\cdot2y + (2y)^{2} = \boxed{9x^{2}+12xy+4y^{2}}\\\\c) \ (2x-4)(2x+4) = (2x)^{2}-4^{2} = \boxed{4x^{2}-16}[/tex]